Judi Online sebagai Ancaman Keamanan Non-Tradisional: Analisis Strain Theory dan Respon Negara Indonesia terhadap Adiksi Digital - Julia Rezeki; Muhammad Naufal Afif (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study examines online gambling as an emerging non-traditional security threat in Indonesia by integrating criminological perspectives, Strain Theory and General Strain Theory, with a state-centric approach in International Relations. Through interviews, field observations, and policy document analysis, the research uncovers how economic pressure, emotional distress, and social normalization drive individuals toward digital gambling addiction. The findings reveal that personal vulnerabilities escalate into broader societal risks, challenging the capacity of state institutions to respond effectively. By mapping these micro-to-macro dynamics, the study exposes the urgent need for a more holistic national strategy, one that moves beyond enforcement and addresses the psychosocial roots of digital gambling.